From Good Goddess to vestal virgins : sex and category in Roman religion - Staples, Ariadne, 1963- (Routledge, 1998)
The role of women in Roman culture and society was a paradoxical one. On the one hand they enjoyed social, material and financial independence and on the other hand they were denied basic constitutional rights. Roman history is not short of powerful female figures, such as Agrippina and Livia, yet their power stemmed from their associations with great men and was not officially recognised. Ariadne Staples' book examines how women in Rome were perceived both by themselves and by men through women's participation in Roman religion, as Roman religious ritual provided the single public arena where women played a significant formal role. From Good Goddess to Vestal Virgins argues that the ritual roles played out by women were vital in defining them sexually and that these sexually defined categories spilled over into other aspects of Roman culture, including political activity. Ariadne Staples provides an arresting and original analysis of the role of women in Roman society, which challenges traditionally held views and provokes further questions.